Lives beyond borders : US immigrant women's life writing, nationality, and social justice - Seethaler, Ina C., 1984- (SUNY series in multiethnic literature., 2021)
A cross-cultural, comparative study of contemporary life writing by women who migrated to the United States from Mexico, Ghana, South Korea, and Iran, Lives beyond Borders broadens and deepens critical work on immigrant life writing. Ina C. Seethaler investigates how these autobiographical texts--through genre mixing, motifs of doubling, and other techniques--challenge stereotypes, social hierarchies, and the supposed fixity of identity and lend literary support to grassroots social justice efforts. Seethaler's approach to literary analysis is both interdisciplinary and accessible. While Lives beyond Borders draws on feminist theory, critical race theory, and disability and migration studies, it also uses stories to engage and interest readers in issues related to migration and social change. In so doing, the book reevaluates the purpose, form, and audience of immigrant life writing. --